The Relationship of Stressors on Academic Stress in Nursing Profession Students of dr. Soebandi University - Amrullah, Akhmad Efrizal; Astutik, Emi Eliya (Journal of Nursing Periodic, 2024)
Introduction: Nursing professional practice carried out by nursing professional students at dr. Soebandi University after completing the educational stage of the undergraduate nursing program. This professional practice must be completed to obtain competency as a professional nurse. Several stressor factors identified include supervisor, study load, study time and study assignments. The aim of this research is to analyze the influence of stressors on academic stress in nursing profession students. Methods: The research design used was a non-experimental design with a descriptive type, where the approach was cross-sectional and carried out at dr. Soebandi University. The sample type in this research is Non-Probability Sample, with a Purposive Sampling method of 30 respondents. Data analysis used the Spearman Rank Correlation test. Results: The hypothesis testing show that study assignments influences the emergence of academic stress. Meanwhile, supervisory factors, study load and study time have no effect on academic stress. Conclusions: Several suggestions can be put forward: providing adequate training to students before carrying out professional practice. Lecturers and supervisors can be more flexible and professional in providing assignments and guidance to students in the nursing profession.